Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10722-017-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Origin of rice (Oryza sativa L.) domestication genes

Abstract: A number of genes that contribute to the domestication traits of cultivated rice have been identified. These include Sh4, Rc, PROG1 and LABA1, which are associated with non-shattering rachis, white pericarp, erect growth and barbless awns, respectively. The mutations giving rise to the “domestication alleles” of these genes are either invariable in cultivated rice, or have variability that is strictly associated with the phenotypic trait. This observation forms the basis to those current rice domestication mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…Furthermore, the amplitude of selection was stronger within japonica than indica population in contrast to aus population and thought to be created historically long time ago. This observation is also in accordance with the recent studies suggesting that aus rice group might have originated from distinct wild progenitor (Civán et al, 2015;Choi et al, 2017;Civáň and Brown, 2017). We suggest that chromosome 5 desert region is very crucial genomic region that might be harbouring important trait loci created by targeted selection, more specifically in japonica and indica genotypes owing to their phylogeographical isolation from aus group during the course of domestication.…”
Section: Multiple Overlapping Selective Sweeps Within Japonica and Insupporting
confidence: 92%
“…Furthermore, the amplitude of selection was stronger within japonica than indica population in contrast to aus population and thought to be created historically long time ago. This observation is also in accordance with the recent studies suggesting that aus rice group might have originated from distinct wild progenitor (Civán et al, 2015;Choi et al, 2017;Civáň and Brown, 2017). We suggest that chromosome 5 desert region is very crucial genomic region that might be harbouring important trait loci created by targeted selection, more specifically in japonica and indica genotypes owing to their phylogeographical isolation from aus group during the course of domestication.…”
Section: Multiple Overlapping Selective Sweeps Within Japonica and Insupporting
confidence: 92%
“…This could have occurred during a single domestication, but equally could have occurred during multiple domestication processes. In agreement with the latter interpretation, we have recently documented multiple genealogical lineages of the Sh4 and Prog1 regions in cultivated rice (Civáň and Brown 2017).…”
supporting
confidence: 87%
“…We agree with this possibility, but excluding the Sh4 upstream region leads again to a paraphyletic tree with similar haplotypes present in indica, japonica and wild rice. Presence of the sh4 'domestication' allele in wild rice (without phenotypic effect) has been confirmed by Sanger sequencing (Zhu et al 2012) and we have shown that the causative SNP pre-dates domestication (Civáň and Brown 2017). It is therefore impossible to infer whether indica obtained the sh4 allele from japonica or its wild progenitor, and the paraphyletic trees in Choi and Purugganan (2018) are inconclusive.…”
mentioning
confidence: 78%
“…Finally, domesticated rice (Oryza sativa L.) has the strongest evidence for polyphyletic origins, with independent, spatially separate domestication in China (japonica gene pool), Indochina to Brahmaputra valley (indica gene pool), and central India to Bangladesh (aus gene pool) [31,32]. Subsequently, there was geneflow between each of these genepools, which may [32] or may not [33] be responsible for the introgression of domestication syndrome traits from the japonica to the indica pool.…”
Section: Centers Of Crop Origin and Domestication Speedmentioning
confidence: 99%
“…Domestication applies selective sweeps on standing genetic variation [81] and on new genetic variation introduced via mutation or introgression. Selection on standing genetic variation might cause the repeated involvement of the same locus in independent domestication events [33] because the selection of favorable alleles that are already present in a wild population usually proceeds faster than new mutations can arise [68,82,83]. On the other hand, new mutations not found in natural populations, possibly detrimental to plant survival, have been identified [39].…”
Section: Domestication Has Left Signatures Both On Morphological As Wmentioning
confidence: 99%